FROM FOOD SAMPLING LOCATIONS TO PEDAGOGY: EXPLORING GEOGRAPHIC DIETARY VARIATIONS AND GAMIFIED LEARNING IN HEALTH ECONOMICS - Jantz, Ronda (My University, 2025)
This Integrated Learning Experience explores two distinct topics, yet both are related to public health initiatives. The first topic involves food and beverage analyte testing through the Food and Drug Administration’s Total Diet Study (TDS) program. The TDS assesses nutrients and contaminants in packaged food and beverage products that are commonly consumed in the United States of America. The foods and beverages were collected from a geographic region across USA. Analyte levels were statistically evaluated using ANOVA and Limit of Detection with the aim to determine whether sampling frequency and location could be reduced without compromising data reliability. Results indicated that regional variations were minimal except for bottled water. The limit of detection analyses indicated that most samples were at or near 0 for contaminants. A gamified leaning experience using cost minimization analysis was created for a healthcare economics graduate classroom. This escape room assignment allows students to work together to cut operational costs for a rural hospital system, specifically looking at chronic care follow-up appointments using Telehealth vs. traditional in-person appointments. The students calculate the lower cost option and then present the option to the Board of Directors for approval using a multimedia presentation. Together, these two projects examine important areas of public health education including food safety surveillance and healthcare cost management.
Keywords: total diet study; cost minimization analysis; healthcare economics education; food safety